Solve: x²/³ - 5x¹/³ + 6 = 0
D Deleted member 4993 Guest Dec 1, 2008 #2 Re: Solve Panama said: Solve: x²/³ - 5x¹/³ + 6 = 0 Click to expand... Substitute: u = x¹/³ and your equation will turn into a quadratic equation - then solve it by your favorite method. Please show us your work, indicating exactly where you are stuck - so that we know where to begin to help you.
Re: Solve Panama said: Solve: x²/³ - 5x¹/³ + 6 = 0 Click to expand... Substitute: u = x¹/³ and your equation will turn into a quadratic equation - then solve it by your favorite method. Please show us your work, indicating exactly where you are stuck - so that we know where to begin to help you.